2017
DOI: 10.1038/ncb3599
|View full text |Cite|
|
Sign up to set email alerts
|

Super-resolution microscopy reveals that disruption of ciliary transition-zone architecture causes Joubert syndrome

Abstract: Ciliopathies, including nephronophthisis (NPHP), Meckel syndrome (MKS) and Joubert syndrome (JBTS), can be caused by mutations affecting components of the transition zone, a ciliary domain near its base that controls the protein composition of its membrane. We defined the three-dimensional arrangement of key proteins in the transition zone using two-color stochastic optical reconstruction microscopy (STORM). NPHP and MKS complex components form nested rings comprised of nine-fold doublets. JBTS-associated muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(178 citation statements)
references
References 70 publications
(85 reference statements)
8
160
1
Order By: Relevance
“…In MEFs, mouse embryonic limb buds and mouse embryonic kidneys, Rpgrip1l deficiency perturbs the amount of members of the Nphp modules at the TZ (Figs A–E, and C–F and M–P), while the TZ amount of the analysed Mks/B9 proteins was unaltered in MEFs and mouse embryonic kidneys (Figs EV3A–E and G–K) bringing up the question whether Rpgrip1l is essential for TZ ultrastructure and TZ function as ciliary gatekeeper in these vertebrate cell types. Previously, it was shown that Rpgrip1l is arranged as discrete clusters in a ring‐like fashion within the TZ (Lambacher et al , ) and a recent report proposed that the components of the Mks/B9 and Nphp modules are localised at the arms of the Y‐links (Shi et al , ). We used TEM to analyse the ultrastructure of the TZ in Rpgrip1l −/− mouse embryonic kidneys and limb buds.…”
Section: Resultsmentioning
confidence: 99%
“…In MEFs, mouse embryonic limb buds and mouse embryonic kidneys, Rpgrip1l deficiency perturbs the amount of members of the Nphp modules at the TZ (Figs A–E, and C–F and M–P), while the TZ amount of the analysed Mks/B9 proteins was unaltered in MEFs and mouse embryonic kidneys (Figs EV3A–E and G–K) bringing up the question whether Rpgrip1l is essential for TZ ultrastructure and TZ function as ciliary gatekeeper in these vertebrate cell types. Previously, it was shown that Rpgrip1l is arranged as discrete clusters in a ring‐like fashion within the TZ (Lambacher et al , ) and a recent report proposed that the components of the Mks/B9 and Nphp modules are localised at the arms of the Y‐links (Shi et al , ). We used TEM to analyse the ultrastructure of the TZ in Rpgrip1l −/− mouse embryonic kidneys and limb buds.…”
Section: Resultsmentioning
confidence: 99%
“…Another type of superresolution microscopy, stochastic optical reconstruction microscopy (STORM), can achieve even higher resolution (~20 nm) than SIM. The high resolution capabilities of STORM enable the detection of spatially distinct proteins within subdomains of cilia, such as the relative positions of distinct ciliopathy-associated complexes within the transition zone [52]. The complementary use of cellular electron microscopy and super-resolution fluorescence microscopy will enable further advancement in our understanding of how subdomains of the ciliary membrane differ from each other.…”
Section: Different Subdomains Of the Cilium Have Distinct Membranesmentioning
confidence: 99%
“…In addition to functions as a diffusion barrier, recent super-resolution microscopy has revealed that the transition zone is a point at which many ciliary membrane-associated proteins accumulate, suggesting that this may be a waypoint at which proteins’ credentials are checked before being allowed entry or turned away (Figure 4) [52,78]. …”
Section: The Transition Zone Controls Ciliary Membrane Protein Composmentioning
confidence: 99%
See 2 more Smart Citations